DEVELOPING ENGLISH LEARNING MODULE THROUGH COMMUNICATIVE LANGUAGE TEACHING (CLT) APPROACH FOR ECONOMICS EDUCATION STUDENTS - Ajah Saputra; Husna Mariani (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
The goal of this research is to create a Communicative Language Teaching based module for Economic Education Department Students of STKIP Muhammadiyah Sampit. The research was carried out in an R&D manner. The data was gathered using questionnaires and documents. The participant of this research was First semester students of Economic Education of STKIP Muhammadiyah Sampit. The researcher Yalden’s model when creating the module that are needs analysis, development, validation and revision, testing, and final revision. A thematic analysis of the qualitative data was performed. According to the findings of the need analysis stage, students need a module to help them mastering English for Economic Education. As a consequence of analysis, the researcher will design and build the materials. The researcher must validate the product before it can be made available to end customers. Finally, the study's findings demonstrate that the modul provided to Economic Education students at STKIP Muhammadiyah Sampit meets their educational needs.